Effectiveness Of Breastfeeding Counseling Training Programs In Efforts To Increase The Competency Of Health Human Resources In West Java - Ratna Sari; Rindu, Rindu; Dina Indriyanti (Jurnal EduHealth, 2024)
One of the main health problems faced by children in Indonesia is malnutrition Malnutrition in toddlers, one of which is caused because in infancy and childhood they do not getting intake in accordance with the best feeding patterns for infants, this shows the need to increase the competence of This shows the need to increase the competence of Human Resources for Health Health Human Resources to improve public knowledge about breastfeeding and increase exclusive breastfeeding coverage. This study aims to determine the breastfeeding counseling training program and to determine and analyze the effectiveness of the breastfeeding counseling training program on improving the competence of Health Human Resources Health Human Resources in West Java region.  A quantitative approach was used with an explanation of relationship between variables. The samples used were grouped based on region of the breastfeeding counseling training participants. Secondary data that is Quantitative secondary data were obtained from Bapelkes Cikarang documentation, annual reports and questionnaires. Data processing was carried out using Microsoft excel and Smart PLS 3 applications. Data analysis using analysis (Structural Equation Modeling) SEM analysis. The results of the research and hypothesis testing illustrate that the training program which includes effective facilitators, organizers and participants has an effect on increasing the competency of breastfeeding counseling training participants and the Facilitator variable through organizing the training plays the most important role in increasing the competency of training participants, this can be seen in the interpretation of the results (Inner Model) indirect relationship where the p value of the Facilitator's influence on increasing competence through implementation is 0.042, this can be interpreted as meaning that there is a significant influence between the Facilitator Variable on increasing Competency through the implementation Variable.